Longitudinal associations of dietary intake with fatigue in colorectal cancer survivors up to 1 year post-treatment, and the potential mediating role of the kynurenine pathway - Holthuijsen, Daniëlle; Rijnhart, Judith J. M.; Bours, Martijn J. L.; van Roekel, Eline H.; Ueland, Per M.; Breukink, Stéphanie O.; Janssen-Heijnen, Maryska Leonie Gertruda; Konsten, Joop L.; Keulen, Eric T. P.; McCann, Adrian; Brezina, Stefanie; Gigić, Biljana; et al. (Brain, behavior and immunity, 2025)
A healthy diet may help to reduce cancer-related fatigue, but evidence is limited and mechanisms remain unclear. Both diet and fatigue following color…
Online veröffentlicht: 7. Februar 2025, Artikelversion: 18. Februar 2025
Gesehen am 11.11.2025